Plasmas Processes Applied on Metals and Alloys - Chen, Jian-Zhang; Chang, Shih-Hang (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on recent advances in plasma technology and its application to metals, alloys, and related materials. Surface modifications, material syntheses, cutting and surface coatings are performed using low-pressure plasma or atmospheric-pressure plasma. The contributions of this book include the discussion of a wide scope of plasma technologies applied to materials. Plasma is a versatile tool that can be applied in many types of material processing. New material processing applications of plasmas and new plasma technologies are being developed rapidly. We hope that this book can contribute new knowledge to the plasma material research society.